The Role of Employee Engagement in The Influence of Leadership Style, Motivation and Work Environment on Employee Performance Of The State Civil Apparatus in The Environment Government of The Riau Islands Province - Prabu Ranto Prihatno Aji; Agustinus Setyawan (Yayasan Riset dan Pengembangan Intelektual, 2024)
Employee performance and quality have a big impact on how well government and public services are managed. As a result, the goal of this research is to improve our understanding of the variables that affect worker performance, with a particular emphasis on the part that employee engagement plays in relation to work environment, motivation, and leadership style. According to this research, increasing employee engagement is essential to raising employee performance. The government sector may get useful insights for developing human resource management strategies by analyzing leadership style, motivation, and work environment as primary elements. In order to enhance employee participation and boost the efficacy and efficiency of public services, it is intended that the findings of this study will aid in the development of management practices and policies.